2020
DOI: 10.1096/fj.201902142r
|View full text |Cite
|
Sign up to set email alerts
|

Deficiency of platelet adhesion molecule CD226 causes megakaryocyte development and platelet hyperactivity

Abstract: This study used constitutive CD226 gene knockout (KO) mice as a model to investigate the functions and mechanisms of CD226 in megakaryocyte (MK) maturation and platelet activation. Although CD226 deficiency did not cause MK polyploidization or platelet granule abnormalities, increased MK counts were detected in the femora bone marrow (BM) and spleen of CD226 KO mice. Particularly, CD226 KO mice have a more extensive membrane system in MKs and platelets than wild-type (WT) mice. We also demonstrated that CD226 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Further study indicated that the deletion of CD226 resulted in mild thrombocytosis and increased MK/platelet number. Platelet hyperactivity was partially due to the decreased platelet-derived nitroxide level in CD226 global knockout mice ( Zhang et al, 2020 ). These findings indicate that CD226 is a potential regulator for intravascular platelet activation to be regarded as antithrombotic agents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Further study indicated that the deletion of CD226 resulted in mild thrombocytosis and increased MK/platelet number. Platelet hyperactivity was partially due to the decreased platelet-derived nitroxide level in CD226 global knockout mice ( Zhang et al, 2020 ). These findings indicate that CD226 is a potential regulator for intravascular platelet activation to be regarded as antithrombotic agents.…”
Section: Discussionmentioning
confidence: 99%
“…PRP was separated at the upper layer from the blood samples by centrifugation at room temperature (RT) for 10 min at 160 g/min. For the preparation of washed platelets, PRP was centrifuged at 2,000 g/min for 10 min at RT, and the platelet pellet was resuspended ( Zhang et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CD226 was expressed on the platelet membrane and was involved in platelet activation [11,12]. Platelets played a crucial role in the control of acute hemorrhage and thrombosis, and thus were involved in atherosclerosis and myocardial infarction [13]. CD226 may participate in atherosclerotic cerebral infarction.…”
Section: Lncrna-mrna Co-expression Network Construction and Hub Genes Analysismentioning
confidence: 99%
“…CD226 was expressed on the platelet membrane and was involved in platelet activation [11,12]. Platelets played a crucial role in the control of acute hemorrhage and thrombosis, and thus were involved in atherosclerosis and myocardial infarction [13]. CD226 may participate in atherosclerotic cerebral infarction.…”
Section: Lncrna-mrna Co-expression Network Construction and Hub Genes Analysismentioning
confidence: 99%